2018
DOI: 10.1016/j.childyouth.2018.09.013
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a sport-based intervention to prevent juvenile delinquency in at-risk adolescents

Abstract: Despite the wide implementation of sport-based crime prevention programs, there is a lack of empirical knowledge on the effectiveness of these interventions. This study evaluated a Dutch sport-based program in N = 368 youth at risk for juvenile delinquency. Intervention effects were tested in a quasi-experimental study, comparing the intervention group with a comparison group using multiple sources of information. The study was conducted under conditions that resemble real-life implementation, thereby enhancin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 52 publications
0
13
0
1
Order By: Relevance
“…Nonexperimental studies have reported on the success of sports-based crime prevention programs ( Hartmann & Depro, 2006 ; McMahon & Belur, 2013 ; Theeboom, De Knop, & Wylleman, 2008 ), but these studies do not permit causal inferences. More recently, the first quasiexperimental study on the effects of a sports-based crime prevention program found positive results on juvenile delinquency ( Spruit, Hoffenaar, Van der Put, Van Vugt, & Stams, 2016 ). Over and above experimental effectiveness research, it is important to examine for whom, how, and under which conditions sports-based crime prevention programs are effective ( Coatsworth & Conroy, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonexperimental studies have reported on the success of sports-based crime prevention programs ( Hartmann & Depro, 2006 ; McMahon & Belur, 2013 ; Theeboom, De Knop, & Wylleman, 2008 ), but these studies do not permit causal inferences. More recently, the first quasiexperimental study on the effects of a sports-based crime prevention program found positive results on juvenile delinquency ( Spruit, Hoffenaar, Van der Put, Van Vugt, & Stams, 2016 ). Over and above experimental effectiveness research, it is important to examine for whom, how, and under which conditions sports-based crime prevention programs are effective ( Coatsworth & Conroy, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Within social work literature, research examining the impact of community sport-based PYD programs for youth who are socially vulnerable and at-risk is promising (Anderson-Butcher et al, 2018; Iachini et al, 2017; Newman et al, 2020; Riley & Anderson-Butcher, 2012; Spruit et al, 2018). For instance, research has demonstrated the impact of community sport-based PYD programs on both intrapersonal and interpersonal life skills.…”
Section: Pyd Through Sport and Recreationmentioning
confidence: 99%
“…One particularly important set of targeted outcomes is life skills. The development of life skills and the ability to transfer the learning of life skills are critical for all youth, especially youth who are socially vulnerable and at risk, as they are disproportionately confronted with a culmination of risk factors and stressors and frequently lack prosocial resources and support (Hermens et al, 2017; Spruit et al, 2018).…”
mentioning
confidence: 99%
“…Juvenile delinquency is a complex, multifactorial problem in today's society, causing considerable financial and societal costs (Spruit, Hoffenaar, van der Put, van Vugt, & Stams 2018). A metaanalytic review showed that once youth committed a crime, they were more likely to develop a persistent pattern of offending (Assink et al 2015;Spruit et al 2018). Moreover, juvenile delinquency often goes with other unwanted developmental outcomes, including educational dropout, unemployment, and health and social problems (Spruit et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A metaanalytic review showed that once youth committed a crime, they were more likely to develop a persistent pattern of offending (Assink et al 2015;Spruit et al 2018). Moreover, juvenile delinquency often goes with other unwanted developmental outcomes, including educational dropout, unemployment, and health and social problems (Spruit et al, 2018). The risk factors for juvenile offending are individual (e.g.…”
Section: Introductionmentioning
confidence: 99%